STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH DIMASA PANDEMI COVID-19 - Ika Karimah; Lisa Iryani (Program Studi Administrasi Bisnis, 2022)
The purpose of this study is to analyze the development strategy of SMEs during the Covid-19 pandemic. The research method used is a qualitative approach. The results in this study are SME development strategies during the covid-19 pandemic in Simpang Ulim District, East Aceh Regency, namely identifying the SME environment, analyzing the SME environment internally and externally based on SWOT analysis, formulating the success measures of the strategies designed based on the analysis. previously, determine goals and targets, measurable, and evaluate various alternative strategies by considering the available resources and external conditions faced and choosing the most appropriate strategy to achieve short-term and long-term goals. The obstacles in the SME development strategy during the COVID-19 pandemic in Simpang Ulim District, East Aceh Regency are marketing difficulties, financial limitations, limited Human Resources (HR) and raw material problems. It is hoped that the government will continue to pay attention to the SME sector so that it continues to grow, the development of SMEs in each region will show the level of success of leaders in advancing their region.